2007
DOI: 10.1007/s11162-007-9061-8
|View full text |Cite
|
Sign up to set email alerts
|

Validating NSSE Against Student Outcomes: Are They Related?

Abstract: While there exist many examples of institutional use of the results of the National Survey of Student Engagement (NSSE), there is a relative paucity of research explicitly linking student outcomes to responses on the survey. A major Doctoral-Extensive institution in the Southeast recently conducted a large-scale implementation of the National Survey of Student Engagement (NSSE). We have linked multiple years of NSSE responses to several student outcomes: freshman retention, GPA, pursuit of graduate education, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 9 publications
6
88
1
2
Order By: Relevance
“…We believe that decision makers ought to be aware of these discussions as to be able to evaluate the rigorousness and appropriateness of the specific survey instruments at their hand. Critics point to two major areas of contention in the student engagement surveys: (1) accuracy of student self-reported information on engagement and learning gains, and (2) the selection of the standards of educational practice and student behaviour implied in the questions (Campbell and Cabrera 2011;Gordon et al 2008;Porter 2013;Porter et al 2011). The proposition on the former is that cognitive abilities of students to comprehend the survey question and retrieve the information are often overestimated by survey designer.…”
Section: Methodological Limitations Of Student Engagement and Experiementioning
confidence: 99%
“…We believe that decision makers ought to be aware of these discussions as to be able to evaluate the rigorousness and appropriateness of the specific survey instruments at their hand. Critics point to two major areas of contention in the student engagement surveys: (1) accuracy of student self-reported information on engagement and learning gains, and (2) the selection of the standards of educational practice and student behaviour implied in the questions (Campbell and Cabrera 2011;Gordon et al 2008;Porter 2013;Porter et al 2011). The proposition on the former is that cognitive abilities of students to comprehend the survey question and retrieve the information are often overestimated by survey designer.…”
Section: Methodological Limitations Of Student Engagement and Experiementioning
confidence: 99%
“…The University also needs to work on improving its performance on student faculty interaction (SFI) and on active and collaborative learning (ACL) and investigate the negative effect they are now having on student satisfaction. Gordon et al (2008) reported a negative correlation between faculty student relationships and senior students with higher GPAs. This finding is also supported by recent research (Arum & Roksa, 2011), where a negative relationship was reported www.ccsenet.org/hes Higher Education Studies Vol.…”
Section: Discussionmentioning
confidence: 98%
“…So it is important to learn which educational practices work best under what circumstances for different types of students in order to improve the quality of student experience and enhance chances of success. Finally, identifying the complex relationship between educational practices, student behaviors, and outcomes is highly needed, as relatively few studies have explored it (Gordon, Ludlum, & Hoey, 2008) and question was not investigated before at the University. In addition and as the University operates in a different cultural and religious context, it is important to investigate the generalizability of student success models and their predictors in a different culture.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the time of taking survey is far from that experience, which may have become obscured over time. Another drawback is that the selection of the standards of educational practice and student behavior implied in the questions is also criticized in the surveys [2]. Therefore, in strategic approaches, institutions should also gather data from external data sources to develop intelligence on students' learning experiences.…”
Section: Introduction *mentioning
confidence: 99%